2021
DOI: 10.2478/rtuect-2021-0011
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Oil-Containing Waste Using Solar Energy

Abstract: Significant oil losses in oil-containing wastes and their adverse impact on the region environmental setting bring about the need to develop an oil-containing wastes treatment technology. To tackle this issue, the authors have set an aim of designing a helio device and creating an oil-containing wastes treatment method based on it to extract oil products. Considering a widespread in the composition and properties of potential oil sludge raw materials and their tendency for either formation of stable emulsions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…In 2021, Abdibattayeva et al [72] designed a helio device, based on solar energy, and used it for a new treatment method to extract oil products from wastewater or solid waste. The following year, Ghouas et al [73] succeeded to remove VOC from aqueous solutions using the cloud point extraction and a biodegradable nonionic surfactant.…”
Section: Resultsmentioning
confidence: 99%
“…In 2021, Abdibattayeva et al [72] designed a helio device, based on solar energy, and used it for a new treatment method to extract oil products from wastewater or solid waste. The following year, Ghouas et al [73] succeeded to remove VOC from aqueous solutions using the cloud point extraction and a biodegradable nonionic surfactant.…”
Section: Resultsmentioning
confidence: 99%
“…4-6). 2 presents relative viscosity that is expressed by the ratio of viscosity of untreated oil to viscosity of heat-treated oil, calculated under the same conditions [21]- [28]. Further analysis showed that heat treatment of flowing oil instantly decreased viscosity.…”
Section: Environmental and Climate Technologiesmentioning
confidence: 99%
“…There are a large number of natural sorbents used to solve water treatment problems, such as quartz sand, activated carbon, chitosan, jute, cellulose, sawdust, bentonite clay, etc. The most common sorbent in domestic and foreign practice for deep purification of drinking water is activated carbons: granular and powdered [11]. But the use of such traditional sorbents in wastewater treatment, in the presence of specific contaminants in the source water, does not provide a guaranteed water quality that meets sanitary rules and regulations.…”
Section: Introductionmentioning
confidence: 99%
“…An analysis of modern literature [ [6], [7], [8], [9], [10], [11], [12], [13]] showed a significant increase in the rate of publications devoted to the study of numerous modifications based on zeolites with the introduction of metal nanoparticles and the scope of the corresponding sorption and catalytic systems. The high surface energy of nanosystems makes them especially attractive for use in many catalytic industries since this property makes it possible to carry out technological processes under milder conditions than traditionally accepted ones.…”
Section: Introductionmentioning
confidence: 99%